Serum YKL-40 in coronary heart disease: linkage with inflammatory cytokines, artery stenosis, and optimal cut-off value for estimating major adverse cardiovascular events - Song, Mowei; Zhang, Guofu; Shi, Hang; Zhu, Erjun; Deng, Li; Shen, Hongtao (Frontiers in Cardiovascular Medicine, 2023)
Objective: YKL-40, previously known as chitinase-3-like protein 1 (CHI3L1), is an inflammation-related glycoprotein that promotes atherosclerosis, but its application and optimal cut-off value as a prognostic biomarker in coronary heart disease (CHD) need more clinical evidence. Thus, this prospective study intended to evaluate the linkage of serum YKL-40 with disease features, inflammatory cytokines, and major adverse cardiovascular events (MACEs) in CHD patients. Methods: Four hundred ten CHD patients were enrolled for serum YKL-40 determination via enzyme-linked immunosorbent assay. Meanwhile, serum YKL-40 in 100 healthy controls (HCs) was also quantified. Results: YKL-40 was increased in CHD patients compared to HCs (P<0.001). YKL-40 was positively linked with hyperlipidemia (P=0.014), diabetes mellitus (P=0.001), fasting blood glucose (P=0.045), C-reactive protein (P<0.001), the Gensini score (P<0.001), and stenosis degree (graded by the Gensini score) (P<0.001) in CHD patients. Additionally, elevated YKL-40 was associated with increased tumor necrosis factor-alpha (P=0.001), interleukin (IL)-1β (P=0.001), IL-6 (P<0.001), and IL-17A (P=0.002) in CHD patients. The 1-/2-/3-year cumulative MACE rates of CHD patients were 5.5%, 14.4%, and 25.0%, respectively. Regarding the prognostic capability, YKL-40 ≥100 ng/mL (the median cut-off value) (P=0.003) and YKL-40 ≥150 ng/mL (the third interquartile cut-off value) (P=0.021) reflected elevated accumulating MACE. While accumulating MACE was not different between CHD patients with YKL-40 ≥80 ng/mL and <80 ng/mL (the first interquartile cut-off value) (P=0.083). Conclusion: Serum YKL-40 positively links with inflammatory cytokines and the Gensini score, whose high expression cut off by 100 ng/mL and 150 ng/mL estimates higher MACE risk in CHD patients.